Junggo qäšqär tori (2016)
Das ist eine Regierungswebseite der Bezirksregierung des Bezirks Kashgar in Xinjiang der Volksrepublik China. Auf dieser Kategorie dieser Webseite werden landwirtschaftliche Anbautechniken vorgestellt. - his is a government website of the Kashgar District Government in Xinjiang, People's Republic of China. In this category of this website, agricultural cultivation techniques are presented.